Accounting outsourcing and its relationship with financial performance of SMEs: Manager and employee perspectives. (4th May 2023) - Rezazade, Faeze; Minutillo, Susannah; Patel, Nirmal
Abstract : There is a gap in the literature related to understanding the relationship between outsourcing of accounting functions and financial performance (productivity and cost efficiency) of SMEs. This study examines the relationship between accounting outsourcing and financial performance in terms of cost efficiency and profitability in SMEs operating in Greater Sydney, Australia. An online survey of employees and managers (N = 80) of Australian SMEs using snowball sampling assessed the demographics, accounting outsourcing, organisational profitability, and cost-effectiveness of these SMEs. Data were analysed using linear regression and correlation analyses. The empirical analysis revealed that the outsourcing of tax services was related to a better financial performance of SMEs in terms of both cost efficiency and profitability. The outsourcing of management accounting functions was beneficial to the productivity of SMEs, whereas the outsourcing of general accounting was not related to higher productivity. Collectively, the findings of this study will assist SMEs in identifying resource gaps and the reasons for turning to external accountancy services to close the gaps and improve their financial performance.